How well do people living with neurodegenerative diseases manage their finances? A meta-analysis and systematic review on the capacity to make financial decisions in people living with neurodegenerative diseases. (August 2021) - Bangma, Dorien F.; Tucha, Oliver; Tucha, Lara; De Deyn, Peter P.; Koerts, Janneke
Highlights: Adequate financial decision-making (FDM) is crucial for independent living. Difficulties with FDM are prominent in people living with a neurodegenerative disease (NDD). FDM is related to global cognition in people living with an NDD. FDM is related to working memory, processing speed and numeracy in people living with an NDD. Multidimensional and ecologically valid FDM tests are needed. Abstract: Self and proxy reported questionnaires indicate that people living with a neurodegenerative disease (NDD) have more difficulties with financial decision-making (FDM) than healthy controls. Self-reports, however, rely on adequate insight into everyday functioning and might, therefore, be less reliable. The present study provides a comprehensive overview and meta-analysis of studies evaluating FDM in people living with an NDD. For this, the reliability of performance-based tests to consistently identify FDM difficulties in people living with an NDD compared to healthy controls is evaluated. Furthermore, the associations between FDM and disease severity, performances on standard measures of cognition and demographics are evaluated. All 47 included articles, consistently reported lower performances on performance-based FDM tests of people living with an NDD (including Alzheimer's disease, mild cognitive impairment, frontotemporal dementia, Parkinson's disease, multiple sclerosis or Huntington's disease) compared to healthy controls. The majority of studies, however, focused on Alzheimer's disease and mild cognitive impairment (k = 38). FDM performance appears to be related to cognitive decline, specifically in working memory, processing speed and numeracy.